2006
DOI: 10.1007/s00432-006-0112-x
|View full text |Cite
|
Sign up to set email alerts
|

Metronomic trofosfamide inhibits progression of human lung cancer xenografts by exerting anti-angiogenic effects

Abstract: Our results show advantages of a metronomic trofosfamide schedule compared to a conventional bolus therapy mainly due to inhibition of angiogenesis. In vitro data show that this mechanism works under normoxic and hypoxic conditions and suggest that this is in part a direct cytotoxic effect on endothelial cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…With respect to the antiangiogenic basis of administering chemotherapy in a low-dose frequent manner, a number of studies have shown that some of the endothelial cells of the tumor's expanding neovasculature undergo apoptosis as a result of exposure to metronomic chemotherapy(1, 2) which presumably leads to the reduction in microvessel density as reported in some studies(1, 10). In addition, proangiogenic/vasculogenic bone marrow-derived cells (CEPs) can be targeted by various metronomic chemotherapy regimens(11-14).…”
Section: Introductionmentioning
confidence: 99%
“…With respect to the antiangiogenic basis of administering chemotherapy in a low-dose frequent manner, a number of studies have shown that some of the endothelial cells of the tumor's expanding neovasculature undergo apoptosis as a result of exposure to metronomic chemotherapy(1, 2) which presumably leads to the reduction in microvessel density as reported in some studies(1, 10). In addition, proangiogenic/vasculogenic bone marrow-derived cells (CEPs) can be targeted by various metronomic chemotherapy regimens(11-14).…”
Section: Introductionmentioning
confidence: 99%
“…As such, metronomic chemotherapy may possess several advantages over conventional chemotherapy, including delaying the onset of acquired drug resistance and reducing host toxicity. Two milestone studies by Browder et al (2000) and by Klement et al (2000) followed by several subsequent studies have illustrated the capacity of different cytotoxic agents to preferably target the endothelial cell compartment of tumors when lower doses were given more frequently (Shaked et al, 2005;Klink et al, 2006).…”
mentioning
confidence: 99%
“…The maximum tolerated dose (MTD) of trofosfamide in continuous oral application has been evaluated in pretreated patients with metastatic lung cancer and has been shown to be 125 mg/m 2 [18]. Increasing evidence supports the clinical efficacy of metronomic therapy for the treatment of breast [19,20] and lung cancer [17,21,22]. While intuitively there should be no disagreement with what constitutes a metronomic therapy, the doses used are empirical.…”
Section: Discussionmentioning
confidence: 99%
“…Trofosfamide has been used for decades in the treatment of a variety of malignant diseases. Apart from the cytotoxic effect of trofosfamide there is also a distinct anti-angiogenic effect, especially if the drug is administered in a metronomic fashion [17]. The maximum tolerated dose (MTD) of trofosfamide in continuous oral application has been evaluated in pretreated patients with metastatic lung cancer and has been shown to be 125 mg/m 2 [18].…”
Section: Discussionmentioning
confidence: 99%